2020
DOI: 10.1108/jhr-07-2019-0156
|View full text |Cite
|
Sign up to set email alerts
|

The potential of using wild edible animals as alternative food sources among food-insecure areas in Indonesia

Abstract: PurposeThis study aims to assess the household food security status and explore the potency of wild edible animals as a food source in the food insecurity–prone area of Bangkalan district, Madura, Indonesia.Approach/methodology/designThis cross-sectional quantitative study used a mixed-method approach. A total of 66 participants were pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(17 reference statements)
1
3
0
Order By: Relevance
“…A study in the rural areas in Central Java reported the use of Varanus sp. as medicinal animal, especially to cure for asthma (Husain and Wahidah, 2019); whereas on Madura Island near Java, consumption of monitor lizard by local residents was reported for coping with food scarcity (Adi et al, 2020). These reports are congruent with results of our internet search on food stalls and resellers distributing water monitor meat and other products (Table 1).…”
Section: Eaten Pest In Karawangsupporting
confidence: 75%
“…A study in the rural areas in Central Java reported the use of Varanus sp. as medicinal animal, especially to cure for asthma (Husain and Wahidah, 2019); whereas on Madura Island near Java, consumption of monitor lizard by local residents was reported for coping with food scarcity (Adi et al, 2020). These reports are congruent with results of our internet search on food stalls and resellers distributing water monitor meat and other products (Table 1).…”
Section: Eaten Pest In Karawangsupporting
confidence: 75%
“…In both of these places, a majority of the edible insect species consumed by local groups were available during the spring and summer months, when agricultural productivity is at its lowest. The same pattern of insect consumption during seasons of crop scarcity has been observed across multiple agricultural populations in sub‐Saharan Africa 68,69 and Indonesia, 70 two regions where people continue to experience high levels of malnutrition. On the other hand, agriculture could affect entomophagy by introducing competing species that can more efficiently meet a group's nutritional demands.…”
Section: Optimal Foraging Theory Suggests a Relationship Between Entomophagy And Ecologymentioning
confidence: 53%
“…These differences are seen in some countries or groups eating wild foods. Food and Agriculture Organization (FAO) (1999) defines wild foods as plants, such as roots and tubers, leaves, vegetables, and fruits, and animals, such as insects, amphibians, reptiles, birds, and mammals, which are not cultivated or reared, underutilised, and gathered for food (Adi et al, 2020). Wild foods have attracted attention worldwide and remain popular due to the advent of COVID-19.…”
Section: Halalsphere International Islamic University Malaysia -Inhartmentioning
confidence: 99%